The Analysis of Factors Influencing Indonesian Exchange Rate, Period 2011-2015 - Dhian Cayadeva Prasetyanandini (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study analyzed the effect of simultaneous and partial variable inflation, interest rates, exports, imports and the money supply to the exchange rate by using multiple linear regression method. Data obtained from the official website of the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). Testing data using classical assumption test to find out that the data used did not have a problem normality, Heterocedasticity, Autocorrelation, and Multicolleanirity. Once the data passes classical assumption test later in the regression using linear regression.The results of this study indicate that by simultaneous variable inflation, interest rates, exports, imports and the money supply significantly influence changes to the exchange rate. In partial only variable inflation, interest rates and the money supply affect exports and imports while the variable has no effect on the movement of the exchange rate.Keywords: Inflation, interest rate, export, impor, money supply, classical assumption test, multiple linear regression.